RESEARCH ON AYURVEDA DRUGS TOWARDS THE DRUG DEVELOPMENT FOR PLASMODIUM VIVAX MALARIA (AYUSHDHARA, 2017)
Developing countries are more vulnerable to the Vector borne diseases, than developed countries. Incidence of Malaria is steadily increasing and number of deaths as well; is a serious problem in Africa; every five (20%) childhood deaths are due to the effects of the disease and every 30 seconds a child dies from malaria. The problem of Malaria acquired new dimensions such as resistance of vectors to chemical insecticides and drug resistance in strains of Plasmodium Vivax and Plasmodium Falciparum. These are the serious obstacles in the control of Malaria and hence there is a serious need to develop alternate strategies to control Malaria.Central Council for Research in Ayurvedic Sciences is carrying out clinical trial on different Vector Borne Diseases like Malaria, Filariasis etc since seventies. Trial carried out with herbal and herbo-mineral drugs like AYUSH-64, Saptaparnatwak ghanavati, Guduci satva, Spatika Bhasma, Kiratatiktadi compound, Parijatapatra ghanavati etc. on Plasmodium Vivax Malaria. The present paper deals with the details of those drugs and concludes the best drug for control of Malaria.